New neolignans and a lignan from Miliusa fragrans, and their anti-herpetic and cytotoxic activities - Sawasdee,K. (Elsevier Limited, 2015)
Seven new neolignans and a new lignan were isolated from the leaves and the stems of Miliusa fragrans, along with nine known polyphenolic compounds. Their structures were established through analysis of spectroscopic data, including 1H and 13C NMR, COSY, NOESY, HSQC, HMBC, and HRMS. The isolates were also evaluated for their inhibitory activity against herpes simplex virus types 1 and 2 (HSV-1 and HSV-2) and their cytotoxicity against KB, MCF7, and NCI-H187 cancer cells. © 2013 Elsevier Ltd. All rights reserved.